Combined effects of fungicides formulations and potato varieties on late blight management, yield and net farm income in Kenya - J. M. Kilonzi; M. W. Nyongesa; R. L. Amata; P. Pwaipwai; D. Githui; S. Omondi; W. Lusike; V. Kirugua; J. J. Mafurah (European Journal of Plant Pathology, 2024)
Management of late blight relies on the use of fungicides and potato varieties which have been associated with loss of efficacy over time. Baseline survey and field studies were conducted to evaluate the effects of fungicide formulations and potato varieties in managing late blight and subsequently on net farm income improvement. Four fungicides formulations (Infinito® (Fluopicolide 62.5g L −1 + propamocarb 625 g L −1 ), Milraz® (Propineb 700 g kg −1 + cymoxanil 60 g kg −1 ), Mistress 72® (Mancozeb 640 g kg −1 + cymoxanil 80 g kg −1 ) and Ridomil® (Metalaxyl 40 g kg −1 + mancozeb 640 g kg −1 )), and varieties (Kenya Mpya, Shangi and Dutch Robijn) were evaluated. Survey results revealed that the majority (78%) of the farmers selected varieties to grow based on market dynamics as compared to seed availability (18%), disease resistance (12%) and other factors (8%). The most widely and least used fungicides were Ridomil® (28.8%) and Infinito® (1.7%) respectively. Late blight significantly reduced crop growth (height and stem count) and yield in the unprotected plots in Shangi and Dutch Robijn, but no effect was observed in K. Mpya. Mistress® suppressed blight symptoms by 54%, while Milraz® (lowest effects) reduced the disease by (43%). In unprotected plots, disease severity on K. Mpya was below 1%, while in Shangi and Dutch Robijn varieties, it was 60 and 78% respectively. Reduction in disease by Mistress® resulted in higher yield (30.70 t ha −1 ) as compared to the unprotected plots (9.25 t ha −1 ). Maximum yield (28.56 t ha −1 ) was obtained from K. Mpya, while Dutch Robijn, had the lowest observed yield (20.70 t ha −1 ) in protected plots. Yet, the highest cost benefit ratio (CBR) was recorded in unprotected plots with K. Mpya. The smallest CBR (1.55) was observed on plots where Milraz® was applied on Dutch Robjn. Results of this study show that, the use of fungicides reduced late blight and improved yield of potato substantially, but the efficacy varied with fungicide formulation and potato variety. However, the use of resistant variety was effective in managing late blight hence a useful tool for minimizing fungicide applications. Therefore, use of resistant variety could enhance a healthy biodiversity and at the same time maximize food production.

Effects of Seed Tuber Size of Potato Varieties on Fungicide Spray Regime, Weed Infestation and Net Farm Income in Potato Production - J. M. Kilonzi; D. Githui; P. Pwaipwai; C. Kawira; S. Otieno; J. Kelele; N. Ng’ang’a; M. Nyongesa; J. Mafurah; A. Kibe (Potato Research, 2024)